2021
DOI: 10.1101/2021.03.12.435183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Primed to Die: An Investigation of the Genetic Mechanisms Underlying Noise-Induced Hearing Loss and Cochlear Damage in Homozygous Foxo3-knockout Mice

Abstract: The prevalence of noise-induced hearing loss (NIHL) continues to increase, with limited therapies available for individuals with cochlear damage. We have previously established that the transcription factor FOXO3 is necessary to preserve outer hair cells (OHCs) and hearing thresholds up to two weeks following a mild noise exposure in mice. The mechanisms by which FOXO3 preserves cochlear cells and function are unknown. In this study, we analyzed the immediate effects of mild noise exposure on wild-type, Fox… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…Prior to this, some animal studies have demonstrated that NOX3, FOXO3, NRF2, CX26, CRFR2, BHMT, A1AR, and MYH14 (Beaulac et al 2021; Fu et al 2016; Graham et al 2010; Honkura et al 2016; Lavinsky et al 2015; Partearroyo et al 2019; Vlajkovic et al 2017; Zhou et al 2016) knockout mice are more sensitive to noise than wild-type mice. These studies in knockout mice have shown that genetic defects in mice, which disturb specific paths and structures within the cochlea, make mice more sensitive to noise (Le et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to this, some animal studies have demonstrated that NOX3, FOXO3, NRF2, CX26, CRFR2, BHMT, A1AR, and MYH14 (Beaulac et al 2021; Fu et al 2016; Graham et al 2010; Honkura et al 2016; Lavinsky et al 2015; Partearroyo et al 2019; Vlajkovic et al 2017; Zhou et al 2016) knockout mice are more sensitive to noise than wild-type mice. These studies in knockout mice have shown that genetic defects in mice, which disturb specific paths and structures within the cochlea, make mice more sensitive to noise (Le et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For ATX, compounds, such as FS-3, CPF-4, and TG-mTMP (18)(19)(20), have been reported as fluorescent substrates, and many inhibitors have been identified (21,22). In contrast, GDE4 has been suggested to be involved in retinitis pigmentosa (23), while GDE7 in fatty liver (24), cancer recurrence (25), and noise-induced hearing loss (26). However, no fluorescent substrates of GDE4 or GDE7 have been reported till date, and their enzymatic activities have been measured by TLC (12,14) and quantification of liberated choline (13),…”
Section: Introductionmentioning
confidence: 99%